The mediating role of compassion fatigue between perceived organization support and caring behavior among outpatient nurses in China: a cross-sectional study - Xingxing Liu; Fang He; Tian Tian; Jun Zhang; Yuanjiao Ji; Yuexia Zhong (BMC Nursing)
Abstract Background The caring behaviors of outpatient nurses play a crucial role in improving the quality of care in hospitals. Work resources and personal psychological resources have a significant impact on nurses’ caring behavior. Previous research has shown that perceived organizational support and compassion fatigue are linked to nurses’ caring behaviors. However, the specific relationship among these variables is less clear in the context of outpatient nurses working in high-stress environments. Methods A convenience sampling method was utilized to recruit 413 outpatient nurses from six tertiary hospitals in Xi’an, China, as research subjects between November 2023 and January 2024. The questionnaires used in the study included a sociodemographic questionnaire, the Perceived Organizational Support Scale, the Chinese version of the Compassion Fatigue Brief Scale, and the Chinese version of the Caring Behavior Scale. Data analysis involved descriptive statistics, Mann-Whitney U test, Kruskal-Wallis H rank-sum test, Spearman correlation analysis, and the PROCESS macro model 4. Results A significant negative correlation was observed between the sense of organizational support and compassion fatigue (ρ=-0.547, P < 0.01). Conversely, a significant positive correlation was found between the sense of organizational support and caring behavior (ρ = 0.469, P < 0.01). Moreover, there was a significant negative correlation between compassion fatigue and caring behavior (ρ=-0.641, P < 0.01). Subsequent mediation analysis demonstrated that compassion fatigue partially mediated the relationship between perceived organizational support and caring behaviors. The overall impact of perceived organizational support on caring behavior (β = 0.363) encompasses both its direct influence (β = 0.131) and the indirect impact mediated by compassion fatigue (β = 0.232). The mediating effect accounts for 63.9% of the total effect. Conclusion Compassion fatigue acts as a partial mediator in the relationship between perceived organizational support and the caring behavior of outpatient nurses. It is essential for nursing managers to effectively manage both the work resources and personal psychological resources of outpatient nurses to improve their caring behaviors in high-stress settings. By improving nurses’ organizational support resources, we can reduce the depletion of their personal psychological resources and alleviate negative emotions such as compassion fatigue. This, in turn, can improve nurses’ caring behavior and ultimately enhance the overall quality of nursing services in the hospital.